2021
DOI: 10.1186/s13046-020-01782-w
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic fatty liver disease inhibited the co-expression of Fmo5 and PPARα to activate the NF-κB signaling pathway, thereby reducing liver injury via inducing gut microbiota disturbance

Abstract: Background Alcohol-induced intestinal dysbiosis disrupts and inflammatory responses are essential in the development of alcoholic fatty liver disease (AFLD). Here, we investigated the effects of Fmo5 on changes in enteric microbiome composition in a model of AFLD and dissected the pathogenic role of Fmo5 in AFLD-induced liver pathology. Methods The expression profile data of GSE8006 and GSE40334 datasets were downloaded from the GEO database. The W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Hub genes are genes that play crucial roles in biological processes. We constructed the coexpression network of overlapped DEGs to screen KIRC-related hub genes according to previous reports [ 49 , 50 ], and the results showed that both PGK1 and CXCR4 are KIRC-related hub genes and highly expressed in KIRC tissues, and there is a strong interaction between PGK1 and CXCR4. The KIRC clinical samples with high mRNA level of PGK1 often own high mRNA expression of CXCR4 correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…Hub genes are genes that play crucial roles in biological processes. We constructed the coexpression network of overlapped DEGs to screen KIRC-related hub genes according to previous reports [ 49 , 50 ], and the results showed that both PGK1 and CXCR4 are KIRC-related hub genes and highly expressed in KIRC tissues, and there is a strong interaction between PGK1 and CXCR4. The KIRC clinical samples with high mRNA level of PGK1 often own high mRNA expression of CXCR4 correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…This endows them with a wide range of roles, including immune functions all over the body and regulations of a specific organ ( Mandard et al, 2004 ). The well-recognized roles in alleviating heart dysfunction and hypertension in the cardiovascular system have been well-characterized ( Goikoetxea et al, 2004 ; Usuda and Kanda, 2014 ), and their abilities to regulate fatty acid transportation and oxidation in the liver have been well-illustrated, further unveiling its association with various kinds of liver injuries ( Botta et al, 2018 ; Kong et al, 2021 ). These could lead to some systematic diseases including diabetes and result in pathological dysfunctions in multiple organs ( R. Moschen et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ERBB signaling pathway was found that it was related to hepatocellular carcinoma [ 24 ] while the progress of hepatocellular carcinoma had a relationship with Notch signaling pathway through a series of target spots [ 25 , 26 ]. Moreover, VEGF signaling pathway [ 27 , 28 ], WNT signaling pathway [ 29 , 30 ] and PPAR signaling pathway [ 31 ] suggested similar results. Such findings showed the biological functions of mRNAs could be regarded as predictable factor for prognosis though more researches and experiments needed to done to verify the hypothesis.…”
Section: Discussionmentioning
confidence: 92%